Análise conformacional da enzima protease do HIV-1 relacionada à resistência ao inibidor Nelfinavir - HOLANDA, Luiz Henrique Campos (Universidade Federal do Pará, 2017)
The Human Immunodeficiency Virus (HIV), which causes acquired immunodeficiency syndrome (AIDS), is a retrovirus that has highly virulent glycoproteins that invade the CD4 + T lymphocyte through its CCR4 and CXCR5 receptors. The biological cycle of HIV is mediated by the protease, transcriptase and integrase enzymes. HIV-1 protease is an enzyme that is present in the final phase of the biological cycle, where virus maturation occurs, and is an important pharmacological target. The main objective of this project is to verify the effects of the D30N, I84A and M46I mutations on the HIV-1 protease enzyme and the complex formation with the nelfinavir inhibitor through molecular dynamics and bioinformatics techniques. The results based on the structural analyzes showed structural differences between the studied systems. The 1OHR system presented a closed conformation, the systems D30N and D30N_I84A_M46I presented semi-open conformation and the D30N_I84A system presented open conformation, in which the latter presented lower free energy value and greater instability in the RMSD analyzes, however the greater flotation of residues Of amino acids. The theoretical analyzes showed the importance in the resistance of the double mutation D30N_I84A and the conformational restructuring capacity of the M46I mutation and catalytic capacity.